As tecnologias digitais na visão institucional dos cursos de letras das universidades federais em Minas Gerais - Reis, Ana Clara Martins Resende dos (2024)
With the outbreak of the pandemic in 2020, due to the Coronavirus, our educational system suffered from the need to modify teaching-learning processes. Thus, with the use of digital technologies there was a commitment to trying an emergency alternative for education. Given that scenario, schools and teachers had to adapt quickly, a hard job, mainly because of the use of digital technologies in the educational system. The panorama made them advance in school spaces. They who, before, slowly entered the classrooms, became essential in emergency teaching. Motivated by this situation, from the perspective of teacher training, the present investigation was developed, in Applied Linguistics, in a documentary and qualitative way. Institutional documents in force at the time that structured the degree in 7 Literature courses at public universities located in Minas Gerais were investigated: Curricular Pedagogical Projects (CPP) and syllabus of their disciplines. The selection is based on those universities whose courses obtained the highest grades in the latest evaluation by the Ministry of Education (MEC), in 2021, namely, Juiz de Fora Federal University (JFFU), Federal University of Lavras (FULA), Federal University University of Minas Gerais (FUMG), Federal University of São João Del Rei (FUSJ), Federal University of Triângulo Mineiro (FUTM), Federal University of Uberlândia (FUU) and Federal University of Viçosa (FUV). Thus, the research had the general objective of identifying the approach to digital technologies in the two types of official documents mentioned, of the seven Languages courses, and mapping their relationship with the training of mother tongue teachers (Portuguese). Specifically, the aim was to problematize the implications and institutional contributions of the courses for teaching in basic education and to map the mentions in Literature courses to digital/digital technologies in their institutional discourses. The analysis was carried out in two parts. Firstly, mentions of TDIC were sought in the PPC, which were analyzed according to the number of references found to understand the main concepts identified. In the second part, we funneled the analysis to the sheets of the curricular components of the selected courses. From this, considerations were made about the appearance of digital technologies in these documents based on the concepts of autonomous and ideological literacy, by Street (1984). In general, we observed that, in institutional discourses, universities have few disciplines that visibly contemplate TDIC, as well as PPC explicitly describe little information about them, which made us reflect and problematize about this aspect in teacher training initial, in Minas Gerais, through this investigation.